Optimized preparation conditions of yttria doped zirconia coatings on potassium ferrate (VI) electrode for alkaline super-iron battery - Zhang, Y.; Zhao, X.; Zhang, S.; Zhang, G.; Liu, Shaomin (Elsevier, 2012)
To enhance the stability of potassium ferrate (VI) (K2FeO4) electrodes and their discharge capabilities in alkaline battery systems, yttria (Y2O3) doped zirconia (ZrO2) (denoted as Y2O3–ZrO2) coatings are utilized to protect the K2FeO4 electrode in alkaline electrolytes. The preparation conditions of Y2O3–ZrO2 coatings on K2FeO4 electrodes are investigated in detail and the optimum preparation conditions are determined. Results of discharge tests with open module batteries show that the Y2O3–ZrO2 coated K2FeO4 electrode (prepared under the optimum conditions) provides a superior discharge specific capacity than uncoated and ZrO2 coated K2FeO4 electrodes. Alternatively, to further explore the practical application of K2FeO4 electrodes, super-iron coin cells are assembled using a Y2O3–ZrO2 coated K2FeO4 electrode as the cathode and zinc foil as the anode. The discharge specific capacity and discharge specific energy of the coin cell with Y2O3–ZrO2 coated K2FeO4 cathode are 169.8 mA h g-1 and 201.9Wh kg-1 respectively, which aresuperior to the MnO2 coin cell. Therefore, the results indicate that Y2O3–ZrO2 coated K2FeO4 cathode is suitable for practical applications in alkaline battery systems. Consequently, the alkaline super-iron battery is expected to become a novel energy resource system that replaces present primary batteries in various electronic devices.